Does irrigation system (Pulsavac™plus) lead to intravascular passage of irrigation fluid during major spine surgery? [Omurga cerrahisinde yikama seti (Pulsavac™plus) i̇le i̇rrigasyonda i̇ntravasküler Alana Sivi geçişi olur mu?] - (:unkn) unknown (My University, 2008)
Aim of this study is to evaluate the passage of irrigation fluid during - irrigation with (Pulsavact™ plus) and its effect on whole blood count and blood electrolytes level. After propofol, remifentanil and vecuronium induction lungs were intubated and prone position was given to the patients. Under sterile condition midline incision was performed, paravertebral muscles were dissected. Following discectomy, decompression of spinal cord and roots; irrigation system was used for five minutes irrigation. Patients were randomized by using sealed envelopes, selected by anesthesiologist, into 2 groups (20 patients in each group); during irrigation 1000ml of 0.9% NaCl+40cc %10 povidon-iyodine followed by 1000ml of 0.9% NaCl in Group S and 1000ml of lactated ringer+40cc %10 povidon-iyodine followed by 1000ml of lactated ringer in Group L were used as an irrigation fluid. Blood samples for whole blood count and Na and Potassium were taken just before and after the instrumentation. Each group hemoglobin and hemotocrit values were dropped after irrigation. For electrolytes, only potasium in Group L was dropped. These data shows that irrigation fluid passes to the intravascular space leading to the decrease in whole blood count. Lactated ringer irrigation leads to increase in potasium. level, but not 0.9% NaCl.
Keywords: Electrolyte imbalance; Instrumentation; Irrigation; Irrigation system; Major spine surgery